2020
DOI: 10.18632/aging.102608
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA copy number profiling and bioinformatics analysis of ovarian cancer reveals key genes and pathways associated with distinct invasive/migratory capabilities

Abstract: Ovarian cancer (OC) metastasis presents major hurdles that must be overcome to improve patient outcomes. Recent studies have demonstrated copy number variations (CNVs) frequently contribute to alterations in oncogenic drivers. The present study used a CytoScan HD Array to analyse CNVs and loss of heterozygosity (LOH) in the entire genomes of 6 OC patients and human OC cell lines to determine the genetic target events leading to the distinct invasive/migratory capacities of OC. The results showed that LOH at Xq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
(63 reference statements)
2
3
0
Order By: Relevance
“…Additionally, a potential mutation site in the domain responsible for heteromerization and transactivation (kinase-induced domain, KID) was demonstrated [ 105 ]. Similar results were reported by Liu et al [ 106 ]. In the study based on PASTA analysis, authors identified potential gene-related transcription factors in ovarian cancer indicating CREB, ATF3, and RFX1 [ 106 ].…”
Section: The Bioinformatics Prediction In Ovarian Cancersupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, a potential mutation site in the domain responsible for heteromerization and transactivation (kinase-induced domain, KID) was demonstrated [ 105 ]. Similar results were reported by Liu et al [ 106 ]. In the study based on PASTA analysis, authors identified potential gene-related transcription factors in ovarian cancer indicating CREB, ATF3, and RFX1 [ 106 ].…”
Section: The Bioinformatics Prediction In Ovarian Cancersupporting
confidence: 92%
“…Similar results were reported by Liu et al [ 106 ]. In the study based on PASTA analysis, authors identified potential gene-related transcription factors in ovarian cancer indicating CREB, ATF3, and RFX1 [ 106 ].…”
Section: The Bioinformatics Prediction In Ovarian Cancersupporting
confidence: 92%
“…RFX1 can inhibit cell migration and invasion by repressing FGF1 in many cancers [ 7 , 70 , 71 ]. Though in the majority of cases, RFX1 acts as a negative regulator of metastasis, it has been reported that the transcriptional activity of RFX1 was doubled in a metastatic ovarian cancer cell line HO-8910PM compared to its parent cell line, suggesting a positive role of RFX1 in cancer metastasis [ 72 ].…”
Section: Rfx1 and Cancermentioning
confidence: 99%
“…Copy number variation (CNV) refers to a form of genomic structural variation that results in abnormal gene copy numbers, including gene amplification, gain, loss and deletion 5 . There is a growing body of evidence indicating that CNVs are related to the genetic and phenotypic diversity of cancers and correlate with the activation of oncogenic drivers and the deletion of tumor suppressors 6‐8 . Based on these findings, CNVs have been used to determine prognosis and subsequent treatment profiles for a number of cancers 9 …”
Section: Introductionmentioning
confidence: 99%
“…5 There is a growing body of evidence indicating that CNVs are related to the genetic and phenotypic diversity of cancers and correlate with the activation of oncogenic drivers and the deletion of tumor suppressors. [6][7][8] Based on these findings, CNVs have been used to determine prognosis and subsequent treatment profiles for a number of cancers. 9 Estrogen-related receptor alpha (ESRRA, also known as ERRα), a member of the ligand-independent orphan nuclear receptor superfamily, is expressed primarily in tissues with high metabolic demand such as skeletal muscle, kidney, heart, liver, and adipose tissue, 10,11 and controls the expression of genes involved in mitochondrial biogenesis and the regulation of cellular energy metabolism, including those encoding enzymes in the tricarboxylic acid cycle, fatty acid oxidation, oxidative phosphorylation, ATP synthesis, and aerobic glycolysis.…”
Section: Introductionmentioning
confidence: 99%